(untitled) (Latakia University Journal -Basic Sciences Series, 2019)
In this article, an iterative numerical technique is suggested for finding the approximate solutions of some Volterra integro-differential equations (VIDEs). Basic idea of proposed method depends on approximating the unknown solution by spline function of degree seventh and using four collocation points. The study shows that the spline solutions of VIDEs are existent and unique, also applied method to test problem is stable and convergent, the convergence rate is seventh with a truncation error . Numerical results are given to illustrate the accuracy and efficiency of the method. Comparisons of the results explain the high accuracy of the proposed spline solution.